Formation of Haloacetonitriles, Haloacetamides, and Nitrogenous Heterocyclic Byproducts by Chloramination of Phenolic Compounds - Nihemaiti, M.; Le Roux, J.; Hoppe-Jones, C.; Reckhow, D.; Croue, Jean-Philippe (American Chemical Society, 2017)
The potential formation of nitrogenous disinfection byproducts (N-DBPs) was investigated from the chloramination of nitrogenous and non-nitrogenous aromatic compounds. All molecules led to the formation of known N-DBPs (e.g., dichloroacetonitrile, dichloroacetamide) with various production yields. Resorcinol, a major precursor of chloroform, also formed di/trichloroacetonitrile, di/trichloroacetamide, and haloacetic acids, indicating that it is a precursor of both N-DBPs and carbonaceous DBPs (C-DBPs) upon chloramination. More detailed experiments were conducted on resorcinol to understand N-DBPs formation mechanisms and to identify reaction intermediates. Based on the accurate mass from high resolution Quadrupole Time-of-Flight GC-MS (GC-QTOF) and fragmentation patterns from electronic impact and positive chemical ionization modes, several products were tentatively identified as nitrogenous heterocyclic compounds (e.g., 3-chloro-5-hydroxy-1H-pyrrole-2-one with dichloromethyl group, 3-chloro-2,5-pyrroledione). These products were structurally similar to the heterocyclic compounds formed during chlorination, such as the highly mutagenic MX (3-chloro-4-(dichloromethyl)-5-hydroxy-2(5H)-furanone) or halogenated pyrroles. To our knowledge, this is the first time that the formation of halogenated nitrogenous heterocyclic compounds is reported from chloramination process. The formation of these nitrogenous byproducts during chloramination might be of concern considering their potential toxicity.